Istraživanje korisnika baštine: međunarodno dijeljenje iskustva i mogućnosti primjene u nas - Stublić, Helena (Array, 2011)
Istraživanje korisnika baštine: međunarodno dijeljenje iskustva i mogućnosti primjene u nas